Results of a Randomized Trial Testing the Efficacy of Tele-Savvy, an Online Synchronous/Asynchronous Psychoeducation Program for Family Caregivers of Persons Living with Dementia. (26th February 2021) - Hepburn, Kenneth; Nocera, Joe; Higgins, Melinda; Epps, Fayron; Brewster, Glenna S; Lindauer, Allison; Morhardt, Darby; Shah, Raj; Bonds, Kalisha; Nash, Rachel; Griffiths, Patricia C
Abstract: Background and Objectives: Family caregivers will grow in number as dementia prevalence increases, underscoring the continued importance of equipping these individuals for their new roles and ameliorating the adverse effects of caregiving. Research Design and Methods: A three-armed, waitlist, randomized trial design tested Tele-Savvy, an online adaptation of a successful in-person psychoeducation program, the Savvy Caregiver. Tele-Savvy is delivered over 43 days to groups of 6–8 caregivers in 7 weekly synchronous sessions accompanied by 36 brief asynchronous video lessons. We enrolled 23 cohorts of 15 eligible caregivers ( N = 261), randomized 2:2:1 to active, attention control, and usual care arms. We assessed caregiver psychological well-being and caregiving mastery at baseline and 3, 6, 9, and 12 months. Multilevel linear models assessed outcomes over the 3 time points examined. The trial was slightly truncated, with Data and Safety Monitoring Board approval, because of the apparent confounding psychological effects of coronavirus disease 2019 restrictions. Results: Study findings indicate statistically and clinically significant benefits to Tele-Savvy arm caregivers (with moderate to large effect sizes) in the areas of depression, perceived stress, reaction to care recipients' behaviors, and enhancement of caregiver mastery. Expected benefits for caregiver burden and anxiety were not found. Discussion and Implications: Findings attest to program efficacy and the viability of employing distance means to improve family caregivers' emotional well-being and sense of mastery in the caregiving role over a 6-month period. Next steps entail finding alternate ways to deliver the program to those with connectivity and/or time constraint problems.